A Systematic Review and Meta-analysis of Mesenchymal Stem Cell Injections for the Treatment of Perianal Crohn's Disease: Progress Made and Future Directions. Issue 5 (May 2018) - Lightner, Amy L.; Wang, Zhen; Zubair, Abba C.; Dozois, Eric J.
Abstract : BACKGROUND: There has been a surge in clinical trials studying the safety and efficacy of mesenchymal stem cells for the treatment of perianal Crohn's disease. OBJECTIVE: The purpose of this work was to systematically review the literature to determine safety and efficacy of mesenchymal stem cells for the treatment of refractory perianal Crohn's disease. DATA SOURCES: Sources included PubMed, Cochrane Library Central Register of Controlled Trials, and Embase. STUDY SELECTION: Studies that reported safety and/or efficacy of mesenchymal stem cells for the treatment of perianal Crohn's disease were included. Two independent assessors reviewed eligible articles. INTERVENTION: The study intervention was delivery of mesenchymal stem cells to treat perianal Crohn's disease. MAIN OUTCOMES MEASURES: Safety and efficacy of mesenchymal stem cells used to treat perianal Crohn's disease were measured. RESULTS: Eleven studies met the inclusion criteria and were included in the systematic review. Three trials with a comparison arm were included in the meta-analysis. There were no significant increases in adverse events (OR = 1.07 (95% CI, 0.61–1.89); p = 0.81) or serious adverse events (OR = 0.53 (95% CI, 0.28–0.98); p = 0.04) in patients treated with mesenchymal stem cells. Mesenchymal stem cells were associated with improved healing as compared with control subjects at primary end points of 6 to 24 weeks (OR = 3.06 (95% CI, 1.05–8.90); p = 0.04) and 24 to 52 weeks (OR = 2.37 (95% CI, 0.90–6.25); p = 0.08). LIMITATIONS: The study was limited by its multiple centers and heterogeneity in the study inclusion criteria, mesenchymal stem cell origin, dose and frequency of delivery, use of scaffolding, and definition and time point of fistula healing. CONCLUSIONS: Although there have been only 3 trials conducted with control arms, existing data demonstrate improved efficacy and no increase in adverse or serious adverse events with mesenchymal stem cells as compared with control subjects for the treatment of perianal Crohn's disease.